(Modified in March 2026) A morphometric, statistical analysis of the morphometric variables of the fourth and fifth order basins in the Tamet basin using geographic information systems. (Journal of Libya for geographical studies, 2022)
The aim of this study is to analyze the morphometric variables of the fourth and fifth order basins in the Tamet Valley, using the Geographical Information System (GIS),  based on the Digital Elevation Model (DEM), with a distinction accuracy of 30 * 30 meters.Through the hydrological analysis of the Digital Elevation Model (DEM), the boundaries of the Tamet Valley basin were determined, the boundaries of its basins of the fourth and fifth orders were also determined, and many morphometric variables were extracted for basins such as the area of ​​the basins, their length, the length of their perimeter and water network, their river order, and the use of mathematical equations applied in this regard in extracting many other morphometric variables.This study also aims to analyze the existing statistical relationships between the morphometric variables of the studied basins using Pearson's Correlation coefficient, and the method of stepwise multiple regression, to reveal the statistical relationships between the morphometric variables of the basins fourth and fifth order  in the basin of Tamet Valley.The present study was divided into five chapters. The first chapter was introductory, and the second devoted to the natural characteristics of the basin of Tamet valley, while the third chapter dealt with the analysis of morphometric variables for the fourth and fifth order of the basins in the Tamet Valley, whereas the fourth chapter included an analysis of the existing statistical relationships between morphometric variables for the above-mentioned basins, as for the fifth chapter, it included the results and recommendations. The study has concluded to extract, calculate, and analyze the morphometric characteristics of the studied basins, where it was shown that the values ​​of these variables were affected by the natural characteristics of the basin of the Tamet  valley, especially the morphometric variables related to the water network. The study has also discovered through statistical analysis the correlational relationships between morphometric variables that are graded in terms of strength starting from strong, medium, and weak relationships, and in terms of type to positive relationships, and negative (inverse) relationships, as well as determining the mutual effects between morphometric variables by applying the method of progressive multiple regression.
Keywords: variables of the fourth and fifth; morphometric; Tamet valley